Calibrated Passive Microwave Daily EASE-Grid 2.0 Brightness Temperature ESDR (CETB) Algorithm Theoretical Basis Document, Version 2.1 ... - Brodzik, Mary J.; Long, David G.; Hardman, Molly A. (NSIDC MEaSUREs Project White Paper, 2024)
This technical document is the Algorithm Theoretical Basis Document for the NASA MEaSUREs Calibrated Passive Microwave Daily EASE-Grid 2.0 Brightness Temperature (CETB) Earth Science Data Record (ESDR) Version 2.0. The document describes the theory of the Radiometer version of Scatterometer Image Reconstruction (rSIR) that was used to produce the CETB ESDR Version 2, an enhanced-resolution, gridded passive microwave data set derived from a suite of satellite-borne sensors operating from 1978 to present. Complete historical Version 2 processing is scheduled for summer 2023, and will be performed using input Global Precipitation Mission (GPM) Level 1C (L1C) products. Version 2 data are managed and distributed at the NASA National Snow and Ice Data Center (NSIDC) Distributed Active Archive Center (DAAC). This ATBD contains the primary material that the NSIDC DAAC has used to compile the data user guide. ...